PENGARUH KUALITAS AUDIT, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2020-2022) - Cahyaningtyas, Haning Oktalia; Dwi Jayanti, Fitri (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2024)
This research aims to determine the influence of Audit Quality, Leverage, and Firm Size on Earnings Management of Banking Companies listed on the Indonesia Stock Exchange for the period 2020-2022. This study employs a quantitative method to test the influence of each variable: Audit Quality, Leverage, and Firm Size on Earnings Management. The data used in this research are secondary data obtained from audited financial reports available on the official website of the Indonesia Stock Exchange. The population of this study comprises all banking companies listed on the Indonesia Stock Exchange. The data collected were processed using SPSS 22. Data analysis techniques include multiple linear regression analysis, descriptive statistical tests, tests of classical assumptions, and hypothesis testing. The results of the study indicate that Audit Quality and Leverage do not significantly influence Earnings Management, while Firm Size significantly influences Earnings Management.